The Effect of QRIS Use on the Safety of Cashless Transactions in UMKM in Bengkulu City - Kresnawati Kresnawati; Jeanifah Triana; Depiana Wulandari; Dea Amanda; Silvana Firtasuli; Yumi Adelia Fateha; Cindy Apriyani Natasya (Journal of Management, Economic, and Accounting, 2026)
Along with the development of digitalization in the banking sector, Bank Indonesia and the Indonesian Payment System Association (ASPI) have created a non-cash payment innovation in the form of QRIS (Quick Response Code Indonesian Standard). QRIS makes it easy for users to make fast and secure digital transactions, especially for Micro, Small and Medium Enterprises (MSMEs). This study aims to analyze the effect of QRIS usage on the safety of cashless transactions among MSMEs in Bengkulu City. The method used is a descriptive quantitative approach, with data collected through interviews and Google Forms. The data obtained from the questionnaire was analyzed using a descriptive statistical approach and simple linear regression testing with the help of IBM SPSS Statistics 27 software.